Zwitter-ion modified glycosaminoglycan-based material, preparation method and application thereof, and hemostatic powder
By using zwitterionic modified aminopolysaccharide materials, using electrostatic interactions and dynamic chemical crosslinking to form an adhesion hydrogel network, the problem that existing hemostasis powders are easily washed away under high-pressure blood flow is solved, and efficient hemostasis and wound healing is achieved.
Patent Information
- Application Number
- CN202411885276.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing hemostatic powders are easily washed away under rapid or high-pressure blood flow, lack sufficient tissue adhesion, and it is difficult to effectively stop bleeding.
Zwitterionically modified aminopolysaccharide-based material is used, which consists of zwitterionically modified aminopolysaccharide-based polymers and oxidized hyaluronic acid. It forms dynamic covalent bonds through electrostatic interactions, hydrogen bonds and Schiff base reactions to achieve rapid gelation and adhesion hydrogel networks of porous structures.
The material can quickly absorb water, gelatinize and effectively adhere to and close the wound, concentrate blood cells, thereby achieving efficient hemostasis and promoting wound healing.
Smart Images

Figure CN119708510A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a zwitterion-modified aminopolysaccharide-based material, a preparation method and application thereof, and a hemostatic powder. Background Art
[0002] Uncontrolled bleeding caused by severe trauma causes more than 2 million deaths worldwide each year, and is one of the main causes of death among civilians and soldiers. The body's inherent coagulation cascade process is difficult to effectively stop heavy bleeding, and the use of hemostatic materials for rapid and effective hemostatic intervention is essential for saving lives.
[0003] At present, a variety of hemostatic materials have been reported, such as gauze, sponges, hydrogels and powders. For most hemostatic materials, it is still difficult to quickly close deep, narrow and irregularly shaped non-pressible wounds. Powdered hemostatic materials have excellent portability and can be directly sprayed and filled in the injured area, which is suitable for hemostasis of non-pressible wounds. However, existing commercialized hemostatic powders such as zeolite-based QuickClot, chitosan-based Celox and starch-based Arista lack sufficient tissue adhesion. This makes these hemostatic powders easily washed away under fast or high-pressure blood flow, seriously hindering their application in hemostasis. Summary of the invention
[0004] The purpose of the present invention is to provide a zwitterion-modified aminopolysaccharide-based material, a preparation method and application thereof, and a hemostatic powder. The zwitterion-modified aminopolysaccharide-based material provided by the present invention has excellent tissue adhesion properties, can effectively stay in the injured area and seal the wound; at the same time, it has excellent water / blood absorption properties, is portable, and can be sprayed.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a zwitterion-modified aminopolysaccharide-based material, comprising a zwitterion-modified aminopolysaccharide-based polymer and oxidized hyaluronic acid;
[0007] The zwitterion-modified aminopolysaccharide-based polymer is obtained by reacting an aminopolysaccharide-based polymer and a zwitterion monomer;
[0008] The mass ratio of the zwitterion-modified aminopolysaccharide polymer to the oxidized hyaluronic acid is 3 / 1 to 1 / 3.
[0009] Preferably, the method for preparing the zwitterion-modified aminopolysaccharide-based polymer comprises the following steps:
[0010] The aminopolysaccharide-based polymer, zwitterionic monomer, initiator and solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a graft copolymerization reaction to obtain a reaction product;
[0011] The reaction product is dialyzed and dried in sequence to obtain the zwitterion-modified aminopolysaccharide-based polymer.
[0012] Preferably, the aminopolysaccharide-based polymer includes any one or more of chitosan, O-carboxymethyl chitosan, chitosan quaternary ammonium salt and hydroxybutyl chitosan.
[0013] Preferably, the zwitterionic monomer is methacrylate sulfobetaine.
[0014] Preferably, the mass ratio of the aminopolysaccharide-based polymer to the zwitterionic monomer is 5 / 1 to 1 / 20.
[0015] Preferably, the mixing comprises the following steps:
[0016] Dissolving the aminopolysaccharide-based polymer in a solvent to obtain an aminopolysaccharide-based polymer solution, wherein the mass percentage of the aminopolysaccharide-based polymer solution is 0.5-5%;
[0017] The aminopolysaccharide-based polymer solution, zwitterionic monomer and initiator are then mixed.
[0018] Preferably, the graft copolymerization reaction temperature is 50-60°C, and the time is 12-24 hours; the graft copolymerization reaction is carried out in a protective gas atmosphere;
[0019] The drying method includes one or more of freeze drying, room temperature drying, vacuum drying and heating drying, and the heating drying temperature is 30-100°C.
[0020] The present invention provides a method for preparing the zwitterion-modified aminopolysaccharide-based material described in the above technical solution, comprising the following steps:
[0021] The zwitterion-modified aminopolysaccharide-based polymer and the oxidized hyaluronic acid are mixed to obtain the zwitterion-modified aminopolysaccharide-based material.
[0022] The present invention provides the use of the zwitterion-modified aminopolysaccharide-based material described in the above technical solution or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method described in the above technical solution in the preparation of hemostatic materials.
[0023] The present invention provides a hemostatic powder, comprising the zwitterion-modified aminopolysaccharide-based material described in the above technical solution or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method described in the above technical solution.
[0024] The present invention provides a zwitterion-modified aminopolysaccharide-based material, comprising a zwitterion-modified aminopolysaccharide-based polymer and oxidized hyaluronic acid; the zwitterion-modified aminopolysaccharide-based polymer is obtained by reacting an aminopolysaccharide-based polymer and a zwitterion monomer; the mass ratio of the zwitterion-modified aminopolysaccharide-based polymer to the oxidized hyaluronic acid is 3 / 1 to 1 / 3. Compared with the prior art, the present invention has the following beneficial effects: the zwitterion-modified aminopolysaccharide-based material provided by the present invention selects zwitterion-modified aminopolysaccharide-based polymer and oxidized hyaluronic acid as key components, and has good hydrophilic properties, so that the zwitterion-modified aminopolysaccharide-based material can quickly absorb tissue fluid. Under water / blood triggering, the zwitterion-modified aminopolysaccharide-based material provided by the present invention can quickly gel under the synergistic effect of non-covalent interaction (electrostatic interaction and hydrogen bond) and covalent interaction (Schiff base reaction). Among them, the electrostatic interaction is provided by the zwitterionic polymer chains in the zwitterionic modified aminopolysaccharide-based polymer structure with negative and positive charges; at the same time, the zwitterionic modified aminopolysaccharide-based polymer can provide a large number of intermolecular and intramolecular hydrogen bonds; in addition, the Schiff base reaction between the aldehyde group in the oxidized hyaluronic acid and the amino group on the aminopolysaccharide-based polymer molecular chain can form dynamic covalent bonds in the gel network. These interactions enable the zwitterionic modified aminopolysaccharide-based material provided by the present invention to absorb liquid and swell, and then construct a hydrogel network structure in situ, thereby forming an adhesive hydrogel network with a porous structure, which can effectively stay in the damaged area and block the wound, which is beneficial to maintaining the wound surface sealed and moist environment, while reducing potential tissue damage and promoting wound healing.
[0025] The present invention provides a method for preparing the zwitterion-modified aminopolysaccharide-based material described in the above technical solution. The raw materials of the preparation method provided by the present invention are easy to obtain, the preparation process is simple, no chemical cross-linking agent is used, and the raw materials have good biocompatibility and biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the polymethacrylate sulfobetaine grafted modified chitosan prepared in Example 1;
[0027] Figure 2 The property changes of the chitosan-based adhesive hemostatic powder grafted with polymethacrylate sulfobetaine prepared in Example 2 in deionized water;
[0028] Figure 3 The water absorption / blood absorption performance of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder prepared in Example 2;
[0029] Figure 4The tissue adhesion of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder prepared in Example 2;
[0030] Figure 5 The biocompatibility of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder prepared in Example 2;
[0031] Figure 6 The in vitro coagulation time of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder prepared in Example 2;
[0032] Figure 7 The red blood cell and platelet adhesion of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder prepared in Example 2. DETAILED DESCRIPTION
[0033] The present invention provides a zwitterion-modified aminopolysaccharide-based material, comprising a zwitterion-modified aminopolysaccharide-based polymer and oxidized hyaluronic acid;
[0034] The zwitterion-modified aminopolysaccharide-based polymer is obtained by reacting an aminopolysaccharide-based polymer and a zwitterion monomer;
[0035] The mass ratio of the zwitterion-modified aminopolysaccharide-based polymer to the oxidized hyaluronic acid is 3 / 1 to 1 / 3.
[0036] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0037] The zwitterion-modified aminopolysaccharide-based material provided by the present invention includes a zwitterion-modified aminopolysaccharide-based polymer. In the present invention, the zwitterion-modified aminopolysaccharide-based polymer is obtained by reacting an aminopolysaccharide-based polymer and a zwitterion monomer. In the present invention, the zwitterion-modified aminopolysaccharide-based polymer is preferably a powder material.
[0038] In the present invention, the method for preparing the zwitterion-modified aminopolysaccharide-based polymer preferably comprises the following steps:
[0039] The aminopolysaccharide-based polymer, zwitterionic monomer, initiator and solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a graft copolymerization reaction to obtain a reaction product;
[0040] The reaction product is dialyzed and dried in sequence to obtain the zwitterion-modified aminopolysaccharide-based polymer.
[0041] The present invention mixes the aminopolysaccharide-based polymer, zwitterionic monomer, initiator and solvent to obtain a mixed solution; and the mixed solution is subjected to graft copolymerization to obtain a reaction product. In the present invention, the aminopolysaccharide-based polymer is preferably a natural aminopolysaccharide-based polymer. The aminopolysaccharide-based polymer preferably includes any one or more of chitosan, O-carboxymethyl chitosan (O-CMCS), chitosan quaternary ammonium salt and hydroxybutyl chitosan, and in the embodiment, it can be chitosan or O-CMCS. The zwitterionic monomer is preferably methacrylic acid sulfobetaine (SBMA). The initiator is preferably ammonium persulfate. The solvent is preferably an acetic acid aqueous solution or water. The mass percentage of the acetic acid aqueous solution is preferably 0.5-1%. The water is preferably deionized water. The mass ratio of the aminopolysaccharide-based polymer and the zwitterionic monomer is preferably 5 / 1-1 / 20, more preferably 2 / 1-1 / 10, and in the embodiment, it can be 1 / 5, 2 / 1, 1 / 1, 1 / 2 or 1 / 10. The mass ratio of the zwitterionic monomer to the initiator is preferably 20 / 1 to 10 / 1. The present invention can ensure that the zwitterionic monomer and the aminopolysaccharide-based polymer are fully grafted and copolymerized by controlling the mass of the aminopolysaccharide-based polymer and the zwitterionic monomer. In the present invention, the mixing preferably includes the following steps: dissolving the aminopolysaccharide-based polymer in a solvent to obtain an aminopolysaccharide-based polymer solution. The mass percentage of the aminopolysaccharide-based polymer solution is preferably 0.5 to 5%, more preferably 0.5 to 2%. After the dissolution, an initial aminopolysaccharide-based polymer solution is obtained. The present invention preferably degasses the initial aminopolysaccharide-based polymer solution with N2 to obtain an aminopolysaccharide-based polymer solution. The temperature of the N2 degassing is preferably 55 to 60°C, and the time of the N2 degassing is preferably 30 to 60 minutes. After obtaining the aminopolysaccharide-based polymer solution, the present invention mixes the aminopolysaccharide-based polymer solution, the zwitterionic monomer and the initiator. In the present invention, the temperature of the graft copolymerization reaction is preferably 50-60°C, and the time is preferably 12-24h; the graft copolymerization reaction is preferably carried out in a protective gas atmosphere, and the protective gas is preferably nitrogen. The graft copolymerization reaction is preferably carried out under stirring. In the present invention, the dialysis is preferably carried out in deionized water, and the molecular weight cutoff of the dialysis bag used for the dialysis is preferably 14000Da. The drying method preferably includes one or more of freeze drying, room temperature drying, vacuum drying and heating drying, and the temperature of the heating drying is preferably 30-100°C. In the present invention, the zwitterion-modified aminopolysaccharide-based polymer obtained by the drying is a powder material.
[0042] In the present invention, one of the raw materials for preparing the zwitterion-modified aminopolysaccharide polymer: the aminopolysaccharide polymer has good water absorption and mechanical strength, and can promote hemostasis by concentrating blood. In addition, the aminopolysaccharide polymer will gradually degrade under the action of enzymes naturally present in body fluids (such as lysozyme and N-acetylglucosaminidase), release N-acetyl-β-D-glucosamine, promote the proliferation and migration of fibroblasts, contribute to the orderly deposition of collagen, and stimulate the increase in the level of natural hyaluronic acid synthesis at the wound site, promoting the re-epithelialization of soft tissue.
[0043] The invention introduces zwitterionic monomers to graft-modify the aminopolysaccharide-based polymer, which can further improve the water absorption performance and the cross-linking performance during subsequent gelation of the obtained zwitterionic modified aminopolysaccharide-based polymer, thereby improving the tissue adhesion of the zwitterionic modified aminopolysaccharide-based material.
[0044] The zwitterion-modified aminopolysaccharide-based material provided by the present invention comprises oxidized hyaluronic acid (OHA). In the present invention, the oxidized hyaluronic acid is preferably a powder material.
[0045] In the present invention, the oxidized hyaluronic acid has good biocompatibility and biodegradability. In addition, it can also promote cell migration and proliferation, thereby promoting tissue regeneration. In the present invention, the mass ratio of the zwitterion-modified aminopolysaccharide-based polymer to the oxidized hyaluronic acid is 3 / 1 to 1 / 3, preferably 1 / 1 to 1 / 3, and can be 1 / 1 or 1 / 3 in the embodiment. The present invention is compounded according to the above-mentioned mass ratio by zwitterion-modified aminopolysaccharide-based polymer and oxidized hyaluronic acid, and the obtained zwitterion-modified aminopolysaccharide-based material can form a hydrosol rapidly by absorbing water, and then trigger the in-situ self-gelation by the synergistic effect of non-covalent interaction (electrostatic interaction and hydrogen bond) and covalent interaction (Schiff base reaction), forming an adhesive hydrogel with a porous structure, so that it can effectively stay in the damaged area and block the wound.
[0046] In the present invention, the zwitterion-modified aminopolysaccharide-based material is preferably a powder material. The zwitterion-modified aminopolysaccharide-based material powder material provided by the present invention can achieve tissue adhesion on the wet tissue surface through a dry cross-linking mechanism; the polymer chains can penetrate into the tissue through rapid liquid absorption and dehydration of the tissue surface, thereby forming entanglements with tissue fibers. At the same time, the removal of water at the wound interface causes the reaction between the aldehyde groups in the hydrogel and the amine groups on the tissue to form stable covalent bonds. Ultimately, the zwitterion-modified aminopolysaccharide-based material provided by the present invention is converted into a viscous hydrogel with a strong adhesion interface, which is beneficial to maintaining wound sealing, maintaining a moist environment, reducing potential tissue damage and promoting wound healing.
[0047] The present invention provides a method for preparing the zwitterion-modified aminopolysaccharide-based material described in the above technical solution, comprising the following steps:
[0048] The zwitterion-modified aminopolysaccharide-based polymer and the oxidized hyaluronic acid are mixed to obtain the zwitterion-modified aminopolysaccharide-based material.
[0049] The present invention has no special requirements on the specific implementation of the mixing of the zwitterion-modified aminopolysaccharide-based polymer and the oxidized hyaluronic acid.
[0050] The present invention provides the use of the zwitterion-modified aminopolysaccharide-based material described in the above technical solution or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method described in the above technical solution in the preparation of hemostatic materials.
[0051] The present invention uses zwitterion-modified aminopolysaccharide-based polymers (i.e., aminopolysaccharide-based polymers modified by zwitterion grafting) and oxidized hyaluronic acid as key components to obtain zwitterion-modified aminopolysaccharide-based powder materials. The zwitterion-modified aminopolysaccharide-based powder materials provided by the present invention can quickly absorb water at the wound, quickly adhere to and seal the wound through electrostatic interaction and dynamic chemical cross-linking, and concentrate blood cells, thereby achieving efficient hemostasis. The zwitterion-modified aminopolysaccharide-based powder materials provided by the present invention have a simple preparation process, good biocompatibility and biodegradability, can be sprayed, have excellent water and blood absorption properties, and are particularly suitable as hemostatic materials for hemostasis and tissue repair of non-pressable wounds.
[0052] The present invention provides a hemostatic powder, including the zwitterion-modified aminopolysaccharide-based material described in the above technical solution or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method described in the above technical solution. The hemostatic powder provided by the present invention can quickly absorb water at the wound, quickly adhere to and seal the wound through electrostatic interaction and dynamic chemical cross-linking, and concentrate blood cells, thereby achieving efficient hemostasis. The hemostatic powder provided by the present invention has a simple preparation process, good biocompatibility and biodegradability, can be sprayed, has excellent water and blood absorption properties, and is particularly suitable as a hemostatic material for hemostasis and tissue repair of non-pressable wounds.
[0053] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1: Preparation of chitosan powder grafted with polymethacrylate sulfobetaine
[0055] Chitosan was dissolved in 1% acetic acid aqueous solution to prepare a 0.5wt% chitosan aqueous solution, and degassed with N2 at 60°C for 30 minutes. Ammonium persulfate and zwitterionic methacrylate sulfobetaine monomer (SBMA) were added to the chitosan aqueous solution in sequence, wherein the mass ratio of chitosan to SBMA was 1 / 5, and the mass ratio of SBMA to ammonium persulfate was 20 / 1. Then, the mixture was stirred for 12 hours at 60°C in a N2 atmosphere, and the polymethacrylate sulfobetaine grafted modified chitosan (CS-g-5PSBMA, abbreviated as CSB5) powder was obtained after dialysis and drying. The polymethacrylate sulfobetaine grafted modified chitosan ( Figure 1 ). Compared with the NMR spectrum of chitosan, the NMR spectrum of CSB5 shows the methyl proton signal of the SBMA main chain (-CH2-C(CH3)-) at about 1ppm, the methylene proton signal at about 2ppm, and the methyl proton signal connected to N at 3.25ppm, i.e. + N(CH3)2, indicating that PSBMA was successfully grafted onto chitosan. The powder has certain tissue adhesion properties, but it cannot form a stable gel under the action of excess body fluids. The powder is lost on the tissue surface and cannot adhere to the tissue. By adjusting the mass ratio of chitosan to SBMA to 2 / 1, 1 / 1, 1 / 2 and 1 / 10, CSB0.5, CSB1, CSB2 and CSB10 powders can be obtained respectively. These powders all have certain tissue adhesion properties. As the SBMA feed ratio increases, the adhesion properties of the obtained CSB powder are enhanced, but all powders cannot form a stable gel under the action of excess body fluids.
[0056] Example 2: Preparation of polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder
[0057] The polymethacrylate sulfobetaine grafted modified chitosan (CSB5) powder prepared in Example 1 was mixed with oxidized hyaluronic acid (OHA) powder in a mass ratio of 1 / 1, and the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder (CSB5-OHA) was obtained after shaking and mixing. Deionized water was dripped on the surface of the powder, and the powder could quickly absorb water, swell and gel ( Figure 2 ). CSB0.5, CSB1, CSB2 and CSB10 powders were mixed with oxidized hyaluronic acid (OHA) powder at a mass ratio of 1 / 1 to obtain CSB0.5-OHA, CSB1-OHA, CSB2-OHA and CSB10-OHA powders respectively. All prepared CSB-OHA powders have excellent water / blood absorption properties (such as Figure 3 It can quickly absorb water and gel and then adhere to the tissue surface, which can seal the wound, quickly stop bleeding and provide a moist environment for the wound, thereby promoting wound healing.
[0058] Example 3: Preparation of O-carboxymethyl chitosan powder grafted with polymethacrylate sulfobetaine
[0059] O-carboxymethyl chitosan (O-CMCS) was dissolved in deionized water to prepare a 1wt% O-CMCS aqueous solution, and degassed with N2 at 60°C for 30 minutes. Ammonium persulfate and zwitterionic methacrylate sulfobetaine monomer (SBMA) were added to the O-CMCS aqueous solution in sequence, wherein the mass ratio of O-CMCS to SBMA was 1 / 5, and the mass ratio of SBMA to ammonium persulfate was 10 / 1. Then, the mixture was stirred at 60°C in a N2 atmosphere for 12 hours, and the polymethacrylate sulfobetaine grafted modified O-carboxymethyl chitosan powder was obtained after dialysis and drying. The powder could not form a stable gel structure under the action of water / blood.
[0060] Example 4: Preparation of polymethacrylate sulfobetaine grafted modified O-carboxymethyl chitosan-based adhesive hemostatic powder
[0061] The polymethacryloyloxyethyl phosphorylcholine grafted modified O-carboxymethyl chitosan powder prepared in Example 3 was mixed with oxidized hyaluronic acid powder at a mass ratio of 1 / 3, and the mixture was shaken and mixed to obtain polymethacrylic acid sulfobetaine grafted modified O-carboxymethyl chitosan-based adhesive hemostatic powder, which had excellent water absorption and water / blood triggered self-gelling properties, and had excellent tissue adhesion.
[0062] Example 5: Performance Test
[0063] 1. Water / blood absorption performance
[0064] The water / blood absorption performance of the polymethacrylate sulfobetaine grafted modified chitosan-based adhesive hemostatic powder (CSB5-OHA, CSB0.5-OHA, CSB1-OHA, CSB2-OHA and CSB10-OHA) prepared in Example 2 within 30 seconds was tested using PBS solution (phosphate buffer solution) with pH = 7.4 or anticoagulated rabbit blood. Figure 3 It can be seen that the adhesive hemostatic powder material CSB-OHA has good water / blood absorption ability. When used for wound hemostasis, it can quickly absorb liquid, adhere to the wound, concentrate blood, and effectively promote hemostasis.
[0065] 2. Tissue Adhesion Performance
[0066] The tissue adhesion strength test was carried out using a universal testing machine to evaluate the adhesion of the CSB-OHA (CSB2-OHA, CSB5-OHA and CSB10-OHA) adhesive hemostatic powder material prepared in Example 2 to the tissue. The tissue adhesion strength test was carried out using a lap shear test. A 1 cm wide piece of fresh pig skin was used, the fat layer was removed with a scalpel, and it was rinsed with PBS (pH = 7.4) for 30 minutes before the test. 15 mg of hemostatic powder was evenly sprayed on the surface of a piece of wet pig skin, and then another piece of pig skin of the same size was used with a bonding area of 10×10 mm 2 After the two pieces of pig skin were gently pressed for 30 seconds at room temperature, the tensile shear strength test was performed on the specimens. The results showed that the CSB-OHA adhesive hemostatic powder material had good tissue adhesion ( Figure 4 ).
[0067] 3. Biocompatibility
[0068] The toxicity of the CSB-OHA (CSB2-OHA, CSB5-OHA and CSB10-OHA) adhesive hemostatic powder prepared in Example 2 to NIH 3T3 cells was tested by the extract method. Before the test, all samples were placed on a clean test bench and sterilized by ultraviolet irradiation for 2 hours. All sterilized samples were immersed in DMEM culture medium in a certain proportion. After obtaining the extract, the extract was used to replace the culture medium for culturing NIH 3T3 cells. After culturing for 24 hours, the proliferation rate of NIH3T3 cells in the well plate was tested with a CCK-8 kit. 0.1mL DMEM culture medium was used as a negative control. Cell experiments showed that CSB-OHA adhesive hemostatic powder had good cell compatibility, and its extract did not affect the growth and proliferation of NIH 3T3 cells.
[0069] The anticoagulated rabbit whole blood was centrifuged at 3000rpm for 10min to prepare a red blood cell suspension. After washing the red blood cells three times with PBS, a 5% (v / v) red blood cell suspension was prepared. Then, CSB-OHA was added to 500μL of the suspension at 0.5g / mL. After incubating the centrifuge tube at 37°C for 1 hour, it was centrifuged at 3000rpm for 5min, and the absorbance of the supernatant was detected. PBS and deionized water were used as negative and positive controls, respectively. The hemolysis experiment showed that the CSB-OHA adhesive hemostatic powder would not rupture red blood cells, and its relative hemolysis rate was less than 5%, which had good blood compatibility ( Figure 5 ). The above results indicate that the CSB-OHA adhesive hemostatic powder prepared in Example 2 has good biocompatibility.
[0070] 4. In vitro coagulation performance
[0071] 50 μL of calcified whole blood was added to a well plate containing 5 mg of sample to evaluate the clotting time of the adhesive hemostatic powder. The blood was incubated at 37°C. The blood was rinsed with PBS at a predetermined time until a stable clot was formed, and this time was defined as the clotting time. Calcified whole blood was used as a blank control group.
[0072] The adhesive hemostatic powder materials (CSB2-OHA, CSB5-OHA and CSB10-OHA) prepared by the present invention were subjected to a dynamic whole blood coagulation index test. 50 μL of calcified whole blood was added to 3 mg of hemostatic powder, incubated in a 37°C water bath for 30 seconds, then 10 mL of deionized water was added and the supernatant was aspirated to measure the absorbance to calculate the coagulation index. 50 μL of heavily calcified whole blood was added to 10 mL of deionized water as a blank control group. The longer the coagulation time, the higher the coagulation index, and the worse the coagulation performance. Figure 6 It can be seen that the coagulation time and coagulation index of CSB-OHA adhesive hemostatic powder material are lower than those of gauze, indicating that CSB-OHA adhesive hemostatic powder material has good in vitro coagulation performance.
[0073] 5. Platelet and red blood cell adhesion properties
[0074] The platelet adhesion performance of the adhesive hemostatic powder material prepared by the present invention was tested. Platelet-rich plasma (50 μL) was added dropwise to the dried CSB-OHA (CSB2-OHA, CSB5-OHA and CSB10-OHA) adhesive hemostatic powder material, followed by incubation at 37°C for 1 hour. Non-adherent platelets were eluted with PBS, and the number of platelets adhered to the CSB-OHA adhesive hemostatic powder material was tested using a lactate dehydrogenase (LDH) kit.
[0075] The adhesive hemostatic powder material prepared by the present invention was tested for its red blood cell adhesion performance. 50 μL of red blood cell suspension was added to 5 mg of hemostatic powder and then incubated at 37°C for 1 hour. Non-adherent red blood cells were washed out with PBS. Then, the sample was immersed in 2 mL of deionized water for 1 hour to lyse the adherent red blood cells, and the supernatant was aspirated to measure the absorbance as the red blood cell adhesion rate. Figure 7 It can be seen that the CSB-OHA adhesive hemostatic powder material has good platelet and red blood cell adhesion properties, which enables the CSB-OHA adhesive hemostatic powder to quickly aggregate platelets and red blood cells when used for wound hemostasis, thereby achieving efficient hemostasis.
[0076] Comparative Example 1 Polymethacrylate sulfobetaine grafted modified chitosan-based mixed hyaluronic acid powder
[0077] The polymethacrylate sulfobetaine grafted modified chitosan (CSB5) powder prepared in Example 1 was mixed with hyaluronic acid (HA) powder in a mass ratio of 1 / 1, and the CSB5 / HA mixed powder was obtained after shaking and mixing. The powder had certain tissue adhesion properties, but under the action of excessive body fluids, the powder was lost on the tissue surface and could not form a gel.
[0078] As can be seen from the above examples, the zwitterion-modified aminopolysaccharide-based material provided by the present invention has zwitterion-modified aminopolysaccharide-based polymers and oxidized hyaluronic acid as key components. It can quickly absorb water at the wound, quickly adhere to and seal the wound through electrostatic interaction and dynamic chemical cross-linking, and concentrate blood cells, thereby achieving efficient hemostasis. At the same time, the zwitterion-modified aminopolysaccharide-based material provided by the present invention has a simple preparation process, good biocompatibility and biodegradability, can be sprayed, has excellent water absorption and blood absorption performance, and is particularly suitable as a hemostatic material for hemostasis and tissue repair of non-pressable wounds.
[0079] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A zwitterion-modified aminopolysaccharide-based material, characterized in that: including zwitterion-modified aminopolysaccharide-based polymers and oxidized hyaluronic acid; The zwitterion-modified aminopolysaccharide-based polymer is obtained by reacting an aminopolysaccharide-based polymer and a zwitterion monomer; The mass ratio of the zwitterion-modified aminopolysaccharide polymer to the oxidized hyaluronic acid is 3 / 1 to 1 / 3.
2. The zwitterion-modified aminopolysaccharide-based material according to claim 1, characterized in that: The preparation method of the zwitterion-modified aminopolysaccharide-based polymer comprises the following steps: The aminopolysaccharide-based polymer, zwitterionic monomer, initiator and solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a graft copolymerization reaction to obtain a reaction product; The reaction product is dialyzed and dried in sequence to obtain the zwitterion-modified aminopolysaccharide-based polymer.
3. The zwitterion-modified aminopolysaccharide-based material according to claim 1 or 2, characterized in that: The aminopolysaccharide-based polymer includes any one or more of chitosan, O-carboxymethyl chitosan, chitosan quaternary ammonium salt and hydroxybutyl chitosan.
4. The zwitterion-modified aminopolysaccharide-based material according to claim 1 or 2, characterized in that: The zwitterionic monomer is methacrylate sulfobetaine.
5. The zwitterion-modified aminopolysaccharide-based material according to claim 1 or 2, characterized in that: The mass ratio of the aminopolysaccharide-based polymer to the zwitterionic monomer is 5 / 1 to 1 / 20.
6. The zwitterion-modified aminopolysaccharide-based material according to claim 2, characterized in that: The mixing comprises the following steps: Dissolving the aminopolysaccharide-based polymer in a solvent to obtain an aminopolysaccharide-based polymer solution, wherein the mass percentage of the aminopolysaccharide-based polymer solution is 0.5-5%; The aminopolysaccharide-based polymer solution, zwitterionic monomer and initiator are then mixed.
7. The zwitterion-modified aminopolysaccharide-based material according to claim 2, characterized in that: The graft copolymerization reaction is carried out at a temperature of 50 to 60° C. and for a time of 12 to 24 hours; the graft copolymerization reaction is carried out in a protective gas atmosphere; The drying method includes one or more of freeze drying, room temperature drying, vacuum drying and heating drying, and the heating drying temperature is 30-100°C.
8. The method for preparing the zwitterion-modified aminopolysaccharide-based material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The zwitterion-modified aminopolysaccharide-based polymer and the oxidized hyaluronic acid are mixed to obtain the zwitterion-modified aminopolysaccharide-based material.
9. Use of the zwitterion-modified aminopolysaccharide-based material according to any one of claims 1 to 7 or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method according to claim 8 in the preparation of hemostatic materials.
10. A hemostatic powder, characterized in that: The invention comprises the zwitterion-modified aminopolysaccharide-based material according to any one of claims 1 to 7 or the zwitterion-modified aminopolysaccharide-based material prepared by the preparation method according to claim 8.
Citation Information
Patent Citations
Preparation method and application of self-thickening bone wound hemostatic gel
CN110464869A
Preparation method and applications of chitosan polypeptide derivative self-cross-linking hydrogel taking oxidized hyaluronic acid as cross-linking agent
CN111019162A
Functionally modified bio-based material as well as preparation method and application thereof
CN118580173A